LENGTH OF STAY OF MUSLIM TOURIST AT HALAL TOURISM DESTINATION: INTEGRATING ISLAMIC ATTRIBUTES WITH PUSH-PULL MOTIVATION AND MEDIATED BY SATISFACTION - Hermawan, Rheza; Tri Ratnasari, Ririn; Huzaini, Moh; Alimusa, La Ode; Njie, Yahya (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2024)
Introduction: The length of stay of tourists is a very critical issue in the tourism and hospitality industries, including in the halal tourism sector. So, this study aims to find out and test the factors that affect the length of stay of Muslim tourists when traveling in halal tourism destinations by integrating Islamic attributes with push-pull motivation mediated by satisfaction. Method: The method used in this study is quantitative using Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis. The population of this study is Muslim tourists who visit halal tourism destinations in Lombok with a sample of 171 respondents. Results: Islamic attributes such as Islamic facilities, alcohol and gambling-free, and Islamic morality have a direct effect on length of stay, while halalness affects the length of stay mediated by satisfaction. Push and pull motivations have a positive effect on the length of stay. Finally, the length of stay is also affected by satisfaction. Conclusion and suggestion: Islamic attributes and motivation as well as satisfaction greatly affect the length of stay of Muslim tourists when traveling at halal tourism destinations. The findings of this study are very important and can serve as a crucial guide for businesses and governments to present the various needs and attributes of Muslim tourists so that they feel satisfied and willing to stay longer in halal tourism destinations.